Characterization and exploited status of some zoobenthos species at the Thi Nai lagoon, Binh Dinh province - Ngai, Phan Duc; Tuan, Vo Si; Tuyen, Hua Thai; Khang, Nguyen An (Academia Journal of Biology, 2015)
The characterization and exploited status of some zoobenthos species at the Thi Nai lagoon, Binh Dinh province was determined by data analysis of previous researchs from 2008-2013 and two additional surveys carried out from 2014-2015. The results showed that 12 benthic animal species that have primarily economic value at the De Gi lagoon, including 5 Bivalvia species, 1 Gastropoda species, 5 Crustacea species and 1 Sipuncula species. Bivalves group make up 77% of the entire commercial yield of benthic animal and possess 96% of the entire yield of benthic animals. Glauconome chinensis, Potamocorbula cf. laevis and Gari elongata possess dominatingly (make up 91% of the entire commercial yield of bivalves). The majority of benthic animal resources are infauna, inhabit in tidal area and concentrate in tidal sandy flats. Yield of benthic animals have decreased seriously. These changes were primarily determined that are caused by the increase of the number and improvement exploited fishing equipments, such as spawning, mesh cage, the machine to exploit Gari elongata and the raking machine and the tightening job. The results of this study could be considered as the scientific basis for futrher studies on the trophic relationship, food web and data for planning, zoning and exploitation of appropriately fisheries resources.